Virtuality: A Theory of Digital Judaism(S). - Margolis, Peter (Modern Judaism: A Journal of Jewish Ideas & Experience, 2023)
Digital media enable new possibilities in Jewish life and lived religion. This "digital Judaism" combines elements of Jewish tradition with the capabilities to create, modify, and transform digital objects in novel ways. It builds on American media history and has been greatly accelerated in response to the exigencies of the COVID-19 pandemic of 2020–2021. The Internet as a form of media functions as an amplifier of human capabilities and Jewish possibilities that can be integrated into Jewish life. This creates the contemporary online–offline media ecology to which I apply the theoretical concept of "virtuality." Virtuality extends and builds upon Heidi Campbell's religious-social shaping of technology (RSST), Michael Satlow's "maps" for defining a Judaism, Uzi Rebhun's study of symbolic Judaism, Ananda Mitra and Rae Lynn Schwatrz's concept of online/offline cybernetic space, and Jack Wertheimer's remix concept.